First report of Kurthia gibsonii in the digestive system of Apis mellifera in an indigenous community in the south of Mexico - David Francisco Lopez; Yanet Romero Ramírez; Miguel Ángel Rodríguez Barrera; Arturo Ramírez Peralta; Renato León Rodríguez; Diana Iveth Orbe Díaz; Alberto Patricio Hernández; Angela Victoria Forero Forero; Jeiry Toribio Jiménez (EUNK Revista Científica de Abejas y Apicultores)
The insect digestive system is an outstanding niche for recognizing and understanding features and interactions with unique microbiota. Apis melliferaplay an important role in honey production and pollination, but their populations have decreased over time, so their study and comprehension are vital. Specimens were collected to study the culturable microbiota of the digestive system in an indigenous community in southern Mexico. Digestive samples of bees from four apiaries were randomly analyzed and cultured, and Gram-positive bacilli were identified through conventional biochemical tests and with molecular markers. Kurthia gibsoniiwas identified in 7.5% (6/80) of the cases, and the sequences obtained were reported in GenBank. This is the first report of K. gibsoniiin the digestive system of bees in apiaries in southern Mexico.